THE PREVALENCE OF TAS2R38 GENE PHENOTYPES AMONG THE PATIENTS WITH SOME ENDOCRINE SYSTEM DISORDERS - Rusudan Khukhunaishvili; Marina Koridze; Sophiko Tskvitinidze; Nato Zosidze; Marina Nagervadze; Irakli Parulava (Rojan GÜMÜŞ, 2017)
PTC (phenylthiocarbamide) is one of the focuses of interest from the medical point of view since a number of associations of the taster/nontaster status of PTC sensitivity with various human diseases have been found. It is estimated that ability of sense of PTC bitterness coded by a single gene TAS2R38. The threshold at which people can taste phenylthiocarbamide (PTC) is bimodal, and some people are tasters while, others are nontasters. In recent years, it is actively conducted the studies of genetic markers in various endocrine disorders. Endocrine diseases, particularly thyroid gland prevalence statistics in Georgia is very high. The goal of our research was to study the phenotype of PTC sensitivity among the patients with some endocrine system disorders in the population of Ajara region of Georgia, particularly diabetes type II and different type of goiter (nodular, diffuse etc.) to reveal any correlation between them. A total of 319 individuals including 136 patients with endocrine system and 183 randomly chosen healthy individuals participated in this study. Obtained results shows, that there is an increased incidence of diffuse toxic goiter in individuals with recessive phenotype of TAS2R38 gene and who are unable to taste PTC bitterness. While, PTC sensibility phenotype inclined to develop nodular goiter. Thus PTC- Sensibility phenotype may be considered one of the genetic markers in the forms of Goiter.